The play of codes and systems in pygmalion: Bernard Shaw and Roland Barthes - Pirnajmuddin, Hossein; Shahpoori Arani, Fatemeh (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
In Pygmalion, George Bernard Shaw deals with the social function of language (linguistic competence) as one of the markers of social status and as a source of social power. Pygmalion’s plot revolves around the linguistic idea of the critical period hypothesis. The linguist in the play bets that the phonetician cannot change the flower girl into a lady by teaching her a genteel language. The phonetician intends to flaunt his power and skill in fashioning a new ‘self’ for the florist girl through linguistic retraining, even though her ’critical period’ is over. Though this acculturation leads to a crisis of personality for the girl, Shaw’s play goes against the hypothesis of ‘critical period’ by showing the possibility of the language retraining of a grown-up girl. Drawing on the theories of Roland Barthes, this article examines the relation between education and the issues of social mobility and cultural codes in the class-conscious society of Pygmalion. Pygmalion could be read as indicating that culture does not come by nature and it is made of codes, which can be taught and learned. Shaw suggests that it is possible to educate lower class people in upper class cultural codes. Moreover, he demonstrates that culture is time-bound and the boundaries between lower and upper class cultural codes were fading at the time so that it was difficult to distinguish a real upper class agent from a fake one.